2003
DOI: 10.1016/s0886-3350(02)01622-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes in eyes with posterior capsule rupture during cataract surgery

Abstract: Most eyes with PCR achieved a good BCVA in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 10 publications
2
57
0
2
Order By: Relevance
“…Ionides et al [2] showed that in the event of capsule rupture, 80% of patients achieved a final visual acuity of 20/40 or better. In terms of patients achieving a BCVA of 6/12 or better at final follow-up, Tan et al [4] reported a figure of 86%, Chan et al [5] reported 87% and, more recently, Ang and Whyte [3] reported a figure of 84.4%. This compares well with our results of 87% of patients reaching this level of acuity at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ionides et al [2] showed that in the event of capsule rupture, 80% of patients achieved a final visual acuity of 20/40 or better. In terms of patients achieving a BCVA of 6/12 or better at final follow-up, Tan et al [4] reported a figure of 86%, Chan et al [5] reported 87% and, more recently, Ang and Whyte [3] reported a figure of 84.4%. This compares well with our results of 87% of patients reaching this level of acuity at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have looked at visual outcome following complicated cataract extraction with vitreous loss, which is the most frequent and significant complication [1][2][3][4][5][6]. Based on their series of complicated extracapsular cataract extractions published in 1988, Balent et al [6] gave a figure of 77.3% of patients achieving 6/12 or better .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, vitreous loss (vitreous breaching the posterior capsule) associated with capsular rupture is a complication that significantly affects postoperative visual acuity. Direct and immediate effects of vitreous loss involve deviation of the pupil (corectopia), inflammation of the anterior chamber, corneal damage, and intraocular pressure elevation; indirect and late effects are cystoid macular edema, vitreous inflammation, and retinal detachment [1][2][3][4][5][6]. Various factors have been reported to associated with this complication [1].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Vitreous loss is associated with an increased risk of sight threatening complications, including cystoid macular oedema, retinal detachment, and endophthalmitis. [4][5][6][7] Posterior capsule disruption may be followed by dislocation of lens fragments into the posterior segment and those eyes have an even worse prognosis. 8,9 Prevention The minutiae of safe cataract surgery are outside the scope of this article and are dealt with in recent texts.…”
Section: Introductionmentioning
confidence: 99%